Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local fractal dimension of collagen detects increased spatial complexity in fibrosis - Dylan T. Casey; Karolyn G. Lahue; Vitor Mori; Jacob Herrmann; Joseph K. Hall; Béla Suki; Yvonne M. W. Janssen-Heininger; Jason H. T. Bates (Histochemistry and Cell Biology, 2024)
Increase of collagen content and reorganization characterizes fibrosis but quantifying the latter remains challenging. Spatially complex structures are often analyzed via the fractal dimension; however, established methods for calculating this quantity either provide a single dimension for an entire object or a spatially distributed dimension that only considers binary images. These neglect valuable information related to collagen density in images of fibrotic tissue. We sought to develop a fractal analysis that can be applied to 3-dimensional (3D) images of fibrotic tissue. A fractal dimension map for each image was calculated by determining a single fractal dimension for a small area surrounding each image pixel, using fiber thickness as the third dimension. We found that this local fractal dimension increased with age and with progression of fibrosis regardless of collagen content. Our new method of distributed 3D fractal analysis can thus distinguish between changes in collagen content and organization induced by fibrosis.

Regional Gas Transport During Conventional and Oscillatory Ventilation Assessed by Xenon-Enhanced Computed Tomography - Jacob Herrmann; Sarah E. Gerard; Joseph M. Reinhardt; Eric A. Hoffman; David W. Kaczka (Annals of Biomedical Engineering, 2021)

Multilevel impact of the dopamine system on the emotion-potentiated startle reflex - Katharina Domschke; Bernward Winter; Agnieszka Gajewska; Stefan Unterecker; Bodo Warrings; Andrea Dlugos; Swantje Notzon; Kathrin Nienhaus; Falko Markulin; Astrid Gieselmann; Christian Jacob; Martin J. Herrmann; et al. (Psychopharmacology, 2015)

Modification of caffeine effects on the affect-modulated startle by neuropeptide S receptor gene variation - Katharina Domschke; Benedikt Klauke; Bernward Winter; Agnes Gajewska; Martin J. Herrmann; Bodo Warrings; Andreas Mühlberger; Katherina Wosnitza; Andrea Dlugos; Swantje Naunin; Kathrin Nienhaus; Manfred Fobker; et al. (Psychopharmacology, 2012)

Erythropoietin: Novel Approaches to Neuroprotection in Human Brain Disease - Hannelore Ehrenreich; Carlotta Aust; Henning Krampe; Henriette Jahn; Sonja Jacob; Manfred Herrmann; Anna-Leena Sirén (Metabolic Brain Disease, 2004)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)